Integrative Blended Learning Framework for Islamic Religious Educationin the Digital Era - Yupande, Putra; Mardhatillah, Annisa; Heru, Heru (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to develop an integrative blended learning framework for Islamic Religious Educationthat systematically combines face-to-face and digital instruction while aligning with character formation and value-based educational objectives in the digital era. Methodology: This study employed qualitative library research using systematic literature review methods. Data were collected from peer-reviewed journal articles, books, and indexed academic databases such as Google Scholar and Scopus. Document analysis, thematic coding, and conceptual synthesis techniques were applied to construct the proposed framework. Main Findings: The findings reveal that blended learning in Islamic Religious Educationrequires structured integration of theoretical foundations, model characteristics, and implementation stages consisting of planning, execution, and evaluation. The framework strengthens student engagement, digital literacy, and value internalization while maintaining the pedagogical objectives of character-based Islamic education. Novelty/Originality of this study: This study offers an integrative conceptual reconstruction of blended learning specifically tailored to Islamic Religious Educationby connecting theoretical foundations, systematic implementation stages, and value-based character formation into a unified framework, advancing existing discussions beyond descriptive implementation and effectiveness studies.